(untitled) (Research, Society and Development, 2021)
Objective: To compare the mobility of patients at admission and discharge, as well as between the General ICU and Covid ICU sectors of a University Hospital in Sergipe, through the analysis of care indicators. Methods: This is a longitudinal observational study developed in 2020. Mobility indicators were obtained from the result of the Mobility Scale in the ICU (IMS). Statistical analysis was performed using the SPSS(11.5) program. To compare the indicators on admission and discharge from the ICUs, the Chi-square and Man Whitney tests were used. Results: At admission, 78.9% in the Covid ICU and 58% in the General had zero IMS. There was an improvement at the time of discharge of 14.6% in Covid and 37.9% in General. As for the time to first standing, the average number of days was 9.8(±8.4) in Covid and 11.2(±9.1) in General. For walking, it was seen that 32% and 23% of the Covid and General ICUs, respectively, walked. There was a significant difference between the General and Covid ICUs only for IMS zero on admission (p=0.021). At discharge, there was no significant difference between the indicators evaluated. In both units no worsening of IMS was observed. Conclusion: It was observed that most patients were admitted to bed, with high rates of zero IMS, with a significant difference between the ICUs. However, at discharge, there was an improvement in the indicators of IMS, with no significant difference between the units, but with still reduced rates, showing an important impairment in the mobility of these patients at discharge from the ICU.